Pathotypes of Pseudoperonospora Cubensis (Berk. et Curt.) Rostow, Causal Agent of Downy Mildew and Induced Defense Responses in the Host - Salati, Mansour (2011)
There is abundant literature on aspects of molecular biology which tended to focus on taxonomic and phylogenetic studies in Oomycete. However, information on local intraspecific populations or pathotype levels of Pseudoperonospora cubensis, the causal agent of downy mildew of cucurbit, is lacking. Host specificity identification is an important aspect of downy mildew disease management, especially for plant breeding purposes and in studies on population biology. Surveys were conducted at five states of West Malaysia to study P. cubensis pathotypes during 2008 and 2009. The sampling sites included farms where cucurbits, such as Cucumis sativus, Cucumis melo, Luffa cylindrica and Trichosanthes cucumerina were grown. Germination test confirmed that only 13 of 29 isolates have the ability to sporulate, and were used for further studies. The results of the present investigation using leaf disc assay showed that there was high variability in P. cubensis pathotypes in West Malaysia (12 pathotypes from 13 isolates in five states). The majority of the isolates obtained in this study were categorized in medium and high pathogenicity groupings, and this illustrates the potential of this pathogen in invading cucurbit fields in tropical regions. Morphological characterization indicated that there is no relationship between pathotype and the size and shape of sporangia. Molecular characterization of the pathotypes based on ITS region revealed that the percent of homology among the 13 isolates and similar sequences from GenBank was high (99%). Phylogenetic analysis of the 13 isolates based on neighbor-joining method on ITS regions revealed five groupings. The highest variation in nucleotide sequence was found in the ITS2 region followed by ITS1, and 5.8S region served as a conserve region with no variation in nucleotide sequence. The phylogram from 13 sequences of COX-II region based on neighbor-joining method categorized isolates into three groupings. The results indicated that both selected regions were inadequate to be used for differentiation of P. cubensis pathotypes. The newly designed species-specific primers on ITS and COX-II regions successfully amplified (528 and 253 bp) rDNA and mitochondria of P. cubensis, respectively. However, no PCR products were obtained for the new designed sets when the primers were tested against different isolates of fungi as negative control including Fusarium solani, Phomopsis langicola, Lasiodiplodia theobromae, Fusarium oxysporum, Pythium sp., Phytophthora sp., Pyricularia oryzae, Aspergillus flavus and Aspergillus niger. A higher activitiy on chitinase and glucanase enzymes was detected on watermelon than cucumber plants at 12 hours after treatment, only with chitosan as an inducer of plant resistance. The results of nitric oxide (NO) and chitinase and glucanase enzymes detection in competitive study showed that increased amount of NO was detected in plants treated with chitosan. Chitinase and glucanase enzymes were also produced in chitosan treated plants with a peak at 12 hours after inoculation with the pathogen. The peak of NO generation in chitosan treatment was 4 hours earlier than the peak of chitinase and glucanase detection. Expression of chitinase and glucanase genes was marked at 4 hours before maximum detection of chitinase and glucanase enzymes, respectively. The NOA expression was conducted based on amplification of NOA associated protein which was designed based on tobacco and potato. Disease assessment confirmed that production of NO in the NO donor treatment (chitosan) plays a critical role in mediating the defense responses in cucumber against downy mildew disease with 58.1% protection. Disruption in NO production would have negative effects on chitinase and glucanase enzymes levels and increase disease incidence up to 60.6% and 71.1% for LNAME and CPTIO treatment, respectively in comparison with control (96.6%). These results demonstrated the there is a relationship between chitinase and glucanase enzymes detection and NO emission in cucumber. The transcript of NOA led to production of NO which suppressed disease incidence. This provides additional evidence for over expression of NOA in cucumber for future study.